Influence of temperature on the properties of one-dimensional piezoelectric phononic crystals. (September 2018) - Nagaty, Ahmed; Mehaney, Ahmed; Aly, Arafa H
Abstract : The current study investigates the influence of temperature on a one-dimensional piezoelectric phononic crystal using tunable resonant frequencies. Analytical and numerical examples are introduced to emphasize the influence of temperature on the piezoelectric phononic crystals. It was observed that the transmission spectrum of a one-dimensional phononic crystal containing a piezoelectric material (0.7 PMN-0.3PT) can be changed drastically by an increase in temperature. The resonant peak can be shifted toward high or low frequencies by an increase or decrease in temperature, respectively. Therefore, we deduced that temperature can exhibit a large tuning in the phononic band gaps and in the local resonant frequencies depending on the presence of a piezoelectric material. Such result can enhance the harvesting energy from piezoelectric materials, especially those that are confined in a phononic crystal.